2011
DOI: 10.1103/physreva.84.022326
|View full text |Cite
|
Sign up to set email alerts
|

Chopped random-basis quantum optimization

Abstract: In this work we describe in detail the Chopped RAndom Basis (CRAB) optimal control technique recently introduced to optimize t-DMRG simulations [1]. Here we study the efficiency of this control technique in optimizing different quantum processes and we show that in the considered cases we obtain results equivalent to those obtained via different optimal control methods while using less resources. We propose the CRAB optimization as a general and versatile optimal control technique. PACS numbers:Realizing artif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
379
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 355 publications
(393 citation statements)
references
References 58 publications
4
379
0
Order By: Relevance
“…This method locates an ostensible QSL at T num QSL = 0.29 after approximately 7.4 · 10 8 trials. This KASS optimization formed our most successful bare computer optimization method, outperforming also the acclaimed CRAB algorithm [27].KASS and CRAB fit the prevalent paradigm of multistarting of local optimizers, while global optimizers are rarely used in quantum optimal control. To investigate the BHW problem using a global optimizer we chose the so-called differential evolution algorithm (DE) due to its demonstrated success in quantum problems [28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method locates an ostensible QSL at T num QSL = 0.29 after approximately 7.4 · 10 8 trials. This KASS optimization formed our most successful bare computer optimization method, outperforming also the acclaimed CRAB algorithm [27].KASS and CRAB fit the prevalent paradigm of multistarting of local optimizers, while global optimizers are rarely used in quantum optimal control. To investigate the BHW problem using a global optimizer we chose the so-called differential evolution algorithm (DE) due to its demonstrated success in quantum problems [28].…”
mentioning
confidence: 99%
“…This method locates an ostensible QSL at T num QSL = 0.29 after approximately 7.4 · 10 8 trials. This KASS optimization formed our most successful bare computer optimization method, outperforming also the acclaimed CRAB algorithm [27].…”
mentioning
confidence: 99%
“…This makes adiabatic evolution significantly exposed to external noise: typically in many-body systems the gap closes with increasing system size N , which implies a dramatic increase of the time required for adiabatic evolutions for large N . Previous studies have demonstrated that optimal control is a powerful tool to drastically reduce the time needed to perform a many-body quantum evolution [15,19]. In particular the Chopped Random Basis (CRAB) technique offers an efficient way to implement optimal control, based on an expansion of the control field onto a truncated basis [14,15].…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that optimal control is a powerful tool to drastically reduce the time needed to perform a many-body quantum evolution [15,19]. In particular the Chopped Random Basis (CRAB) technique offers an efficient way to implement optimal control, based on an expansion of the control field onto a truncated basis [14,15]. Recently it has been shown that optimal control allows for reaching the Quantum Speed Limit (QSL), the minimal time required by physical constraints to perform a given transformation, in spin chains [19,20], cold atoms in optical lattices [21], Bose-Einstein condensates in atom chip experiments and in crossing of quantum phase transitions [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation